Epoxy resin coating material suitable for lean oil lubrication high-load and high-speed working conditions as well as preparation method and application of epoxy resin coating material

By adding nano-scale metal oxides, sub-micron-level solid lubricants and micron-level high-entropy alloy particles to epoxy resin, a three-scale epoxy resin composite material was prepared, which solved the problem of motion mechanisms under lean oil lubrication, high load and high speed conditions. eliminates friction and wear problems and achieves significant improvements in wear resistance and lubrication performance.

CN119331482AActive Publication Date: 2025-01-21SHANDONG RUNZHI NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411455670.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively extend the service life of the moving mechanism under oil-reducing lubrication and high-load and high-speed operating conditions, and conventional friction-reduction and wear-resistant technologies are difficult to control the reliability of the moving mechanism.

Method used

By adding nano-grade metal oxides, sub-micron lubricants, and micron-grade high-entropy alloy particles to the hydroxyl silicone oil-modified bisphenol A. Resin composite material provides a wear -resistant effect.

Benefits of technology

This material can significantly reduce the friction coefficient and wear rate, improve the abrasion resistance and lubrication performance of composite materials, extend the service life of the motion institution and improve its reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331482A_ABST
    Figure CN119331482A_ABST
Patent Text Reader

Abstract

The invention discloses an epoxy resin coating material suitable for lean oil lubrication high-load and high-speed working conditions, which is prepared by the following method: adding a metal oxide with the particle size of 50-100nm into hydroxyl silicone oil modified bisphenol A epoxy resin, uniformly stirring, and grinding to obtain mixed slurry A; then adding a solid lubricant with the particle size of 0.2-2 mu m, uniformly stirring, and grinding to obtain mixed slurry B; and then adding the high-entropy alloy, uniformly stirring, and grinding to obtain the high-entropy alloy. The epoxy resin coating material is applied to preparation of a wear-resistant coating. The epoxy resin coating material is a'large micron-submicron-nano 'three-scale polymer coating composite material formed by coupling high-entropy alloy particles, a solid lubricant and metal compound particles in hydroxyl silicone oil modified bisphenol A type epoxy resin, the surface of a workpiece is coated with the epoxy resin coating material, and the wear-resistant material is obtained after curing. The lubricating oil has excellent wear resistance and lubricating performance and is suitable for lean oil lubrication high-speed and high-load working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an epoxy resin coating material suitable for lean oil lubrication high load and high speed working conditions and a preparation method and application thereof, belonging to the technical field of epoxy resin composite materials. Background Art

[0002] With the continuous and rapid development of high-end equipment technology, more and more harsh operating conditions between moving mechanisms have been proposed by technicians. In the field of friction lubrication, boundary lubrication, lean lubrication and even dry friction conditions frequently occur. Such harsh conditions are more common in large-scale high-end equipment fields such as aerospace and wind power generation. The service life of moving mechanisms faces huge challenges. Conventional friction reduction and wear resistance technologies are difficult to significantly extend the service life of the mechanism, and the reliability of moving mechanisms is becoming increasingly difficult to control. Based on the above problems, polymer-based composite materials have begun to be widely used on the surface of moving workpieces due to their excellent self-lubrication, mature production methods and convenient construction methods, especially in the field of sliding bearings. Mass application has begun to appear.

[0003] Bisphenol A epoxy resin has excellent stability, good processability, high bonding strength, low shrinkage, high mechanical strength and excellent electrical insulation. Researchers have conducted a lot of modification studies on bisphenol A epoxy resin. For example, bisphenol A epoxy resin has been modified through polyether, polyurethane, phenolic formaldehyde, silicone resin and other means.

[0004] High entropy alloys are a mixture of multiple metal elements in equal or nearly equal atomic ratios, and are usually prepared by arc melting, high-frequency induction, powder metallurgy, laser cladding, 3D printing, etc. Many researchers have found that high entropy alloys have great application potential in terms of strength-plasticity, wear resistance, corrosion resistance, high temperature resistance, and radiation resistance. In particular, high entropy alloys with a single FCC phase structure coupled with multiple metal elements can maintain high strength while having good plastic deformation capabilities.

[0005] Many studies have shown that transition metal elements can act as catalysts to promote the construction of carbon-based transfer films on the dual surfaces during the friction process of polymer composites. The Ni element can be quickly transferred to the dual surface to form dense NiO at the bottom of the friction pair, further promoting the dehydrogenation and fracture of polyolefin molecules in the tribochemical reaction, and accelerating the growth of other transfer films above the bottom transfer film.

[0006] As an important catalyst, Co is widely used in organic synthesis, metal organic chemistry, chemical energy and materials science, and has been proven to play an important role in promoting the growth of carbon-based materials. Under harsh working conditions, under the synergistic effect of lubricating medium, speed, pressure and temperature, Cr can quickly form compounds with different valence states. These compounds have the property of easily undergoing redox reactions in catalytic reactions, which makes chromium-based catalysts very good at catalyzing various redox reactions, further helping the rapid construction of transfer films.

[0007] At present, the micro-nano dual-scale design of fillers has been widely used in the application of polymer self-lubricating composites, but the design of the three scales of "large micron-submicron-nano" is rarely mentioned. Summary of the invention

[0008] In view of the above-mentioned prior art, the present invention provides an epoxy resin coating material suitable for lean lubrication, high-load and high-speed working conditions, and a preparation method and application thereof.

[0009] The present invention is achieved through the following technical solutions:

[0010] A method for preparing an epoxy resin coating material suitable for lean lubrication, high load and high speed working conditions, comprising the following steps:

[0011] (1) adding a metal oxide (nanoscale) with a particle size of 50 to 100 nm to a hydroxy silicone oil-modified bisphenol A epoxy resin in an amount of 1 to 10% (weight percentage) of the hydroxy silicone oil-modified bisphenol A epoxy resin, stirring and grinding the mixture to obtain a mixed slurry A;

[0012] The metal oxide is selected from any one or more of titanium dioxide, aluminum nitride, and aluminum oxide, and acts as a catalyst for the construction of a multilayer transfer film;

[0013] (2) adding a solid lubricant (submicron grade) with a particle size of 0.2 to 2 μm to the mixed slurry A in an amount of 1 to 10% (by weight) of the hydroxy silicone oil-modified bisphenol A epoxy resin, stirring and grinding the mixture to obtain a mixed slurry B;

[0014] The solid lubricant is selected from any one or a combination of two or more of MoS2, BN, WS2, talc, and graphite;

[0015] (3) adding high entropy alloy particles (micrometer size) to the mixed slurry B, the added amount being 5% to 50% (weight percentage) of the hydroxy silicone oil-modified bisphenol A type epoxy resin, stirring and grinding to obtain an epoxy resin coating material;

[0016] The high entropy alloy is a CrFeCoNi single-phase FCC structure high entropy alloy.

[0017] Furthermore, in the step (1), the metal oxide is titanium dioxide, the particle size is 50 nm, and the addition amount is 2.5%.

[0018] Furthermore, in the step (2), the solid lubricant is graphite, with a particle size of 1 μm and an addition amount of 2.5%.

[0019] Furthermore, in the step (3), the addition amount of the CrFeCoNi single-phase FCC structure high entropy alloy is 15%.

[0020] Furthermore, the CrFeCoNi single-phase FCC structure high entropy alloy is prepared by the following method: taking four metal powders of Cr, Fe, Co and Ni, the molar ratio of the four metal powders is 1:1:1:1; using an electric arc furnace to melt the metal powders: evacuating the furnace, and when the vacuum degree reaches 1×10 -2 After Pa, the metal powder began to melt at a temperature of 1900-2000°C for 30 minutes; then, the CrFeCoNi single-phase FCC structure high entropy alloy powder was prepared by metal atomization technology.

[0021] Furthermore, the purity of the metal powder is ≥99.5%.

[0022] Furthermore, the specific method of preparing the CrFeCoNi single-phase FCC structure high entropy alloy powder using metal atomization technology is: using a nitrogen-argon mixed gas flow (the molar ratio of nitrogen and argon is 1:9) to impact the metal liquid, the superheat of the alloy is controlled at 100-250°C, and the atomization nozzle pressure is 3-6MPa, thereby obtaining the CrFeCoNi single-phase FCC structure high entropy alloy powder.

[0023] Furthermore, in the step (1), the bisphenol A epoxy resin modified with hydroxy silicone oil is prepared by the following method: in a nitrogen atmosphere, heating the bisphenol A epoxy resin to 100-180° C., stirring (1000-2000 r / min) and adding hydroxy silicone oil during stirring, wherein the mass ratio of bisphenol A epoxy resin to hydroxy silicone oil is 4:1; then adding 0.1%-2.0% (weight percentage, based on the total weight of bisphenol A epoxy resin and hydroxy silicone oil) of a reaction catalyst, stirring the reaction for 0.5-12 hours, and obtaining the bisphenol A epoxy resin modified with hydroxy silicone oil; the reaction catalyst is selected from dibutyltin dilaurate or stannous isooctanoate.

[0024] Furthermore, in the steps (1), (2) and (3), the stirring speed is 1000-2000 r / min, and a vacuum high-speed stirrer can be used. Furthermore, the stirring speed is 1500 r / min, and the stirring time is 10 min.

[0025] Furthermore, in the steps (1), (2) and (3), grinding is performed using a three-roll grinder, wherein in step (1), the grinding spacing is 5 to 10 μm and the rotation speed is 300 r / min; in step (2), the grinding spacing is 5 to 10 μm and the rotation speed is 300 r / min; in step (3), the grinding spacing is 40 to 60 μm and the rotation speed is 300 r / min.

[0026] The epoxy resin coating material prepared by the above method is used in the preparation of wear-resistant coatings. In specific applications, the epoxy resin coating material is coated on the surface of a workpiece and cured.

[0027] Furthermore, in specific applications, epoxy resin low-temperature curing agent is added to the epoxy resin coating material, and then a diluent is added to dilute it, and then it is coated on the surface of the workpiece.

[0028] Furthermore, the epoxy resin low-temperature curing agent is selected from any one of an amine curing agent, an anhydride curing agent or an amide curing agent, and the content is determined according to the actual amount of epoxy resin.

[0029] Furthermore, the diluent is selected from any one or more of acetone, ethanol, n-butanol and xylene.

[0030] The epoxy resin coating material of the present invention is a "large micron-submicron-nano" three-scale polymer coating composite material in which high entropy alloy particles, solid lubricants and metal compound particles are coupled in bisphenol A epoxy resin modified by hydroxy silicone oil. The bisphenol A epoxy resin modified by hydroxy silicone oil can provide friction reduction and wear resistance under oil-poor or even dry friction conditions by relying on the self-lubricating properties of the epoxy resin itself and the dual lubrication mode of releasing silicone oil. The addition of micron-level high entropy alloy can significantly improve the reinforcing effect of bisphenol A epoxy resin. The addition of submicron-level solid lubricants and nanometer-level metal oxide particles can synergistically improve the wear resistance and lubrication properties of the composite material, thereby solving the friction and wear problems under oil-poor and dry friction conditions before the transfer film is formed.

[0031] The preparation method of the epoxy resin coating material of the present invention comprises the following steps: chemically grafting and modifying bisphenol A epoxy resin, coupling high entropy alloy particles, solid lubricants and metal compound particles in the modified matrix, preparing a "large micron-submicron-nanometer" three-scale epoxy resin composite material, and uniformly dispersing the filler in the resin matrix to form a polymer slurry through vacuum high-speed stirring and three-roll grinding and other technologies. In specific applications, after the slurry is coated on the surface of a workpiece and cured, an epoxy resin-based wear-resistant material can be obtained, which has a low friction coefficient and wear rate, excellent wear resistance and lubrication properties, and is suitable for lean oil lubrication high-speed and high-load working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1: Friction coefficient bar graph under lean oil conditions, high speed and high load.

[0033] Figure 2 : Wear rate bar chart under lean oil condition, high speed and high load. DETAILED DESCRIPTION

[0034] The present invention will be further described below in conjunction with the embodiments. However, the scope of the present invention is not limited to the following embodiments. It will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention.

[0035] The instruments, reagents, materials, etc. involved in the following embodiments, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.

[0036] The bisphenol A epoxy resin used in the present invention is commonly purchased from Nantong Xingchen WSR6101.

[0037] The PA650 curing agent used in the present invention is conventionally purchased from Dingyuan County Danbao Resin Co., Ltd.

[0038] The hydroxy silicone oil used in the present invention is conventionally purchased from Dow Corning PMX-0156.

[0039] Comparative Example 1 Preparation of Bisphenol A Epoxy Resin Coating

[0040] Bisphenol A epoxy resin and PA650 curing agent were mixed in a mass ratio of 5:4, and diluted with a n-butanol-xylene mixed solution (the mass ratio of n-butanol to xylene was 4:1) to a viscosity of 1000 cps.

[0041] Comparative Example 2 Preparation of bisphenol A epoxy resin coating modified with hydroxy silicone oil

[0042] Here are the steps:

[0043] (1) Take bisphenol A epoxy resin and put it into a four-necked flask containing a constant pressure feeding funnel, a thermometer and a condensing device. Under a nitrogen atmosphere, heat the bisphenol A epoxy resin to 160° C. and stir it at a speed of 1000 r / min. Add hydroxy silicone oil during stirring, wherein the mass ratio of bisphenol A epoxy resin to hydroxy silicone oil is 4:1; after stirring evenly, add 0.3% dibutyltin dilaurate as a reaction catalyst (0.3% means that the amount of reaction catalyst added is 0.3% of the total weight of bisphenol A epoxy resin and hydroxy silicone oil), stir and react for 4 hours to obtain bisphenol A epoxy resin modified with hydroxy silicone oil;

[0044] (2) The bisphenol A epoxy resin modified with hydroxy silicone oil was mixed with the PA650 curing agent in a mass ratio of 5:4, and diluted with a n-butanol-xylene mixed solution to a viscosity of 1000 cps.

[0045] Comparative Example 3 Preparation of high entropy alloy filled hydroxy silicone oil modified bisphenol A type epoxy resin coating

[0046] Here are the steps:

[0047] (1) Preparation of bisphenol A epoxy resin modified with hydroxy silicone oil

[0048] Same as step (1) of Comparative Example 2.

[0049] (2) Preparation of CrFeCoNi single-phase FCC structure high entropy alloy

[0050] Take four kinds of metal powders (purity of metal powders ≥ 99.5%), the molar ratio of the four metal powders is 1:1:1:1; use an electric arc furnace to melt the metal powders: evacuate the furnace, and when the vacuum degree reaches 1×10 -2 After Pa, the metal powder began to melt at a temperature of 1950°C for 30 minutes; then, the CrFeCoNi single-phase FCC structure high entropy alloy powder was prepared by metal atomization technology: a nitrogen-argon mixed gas flow (the molar ratio of nitrogen and argon was 1:9) was used to impact the metal liquid, the superheat of the alloy was controlled at 150°C, and the atomization nozzle pressure was 5 MPa, thereby obtaining CrFeCoNi single-phase FCC structure high entropy alloy powder. After testing, the particle size was 20-25 μm.

[0051] (3) adding micron-sized high entropy alloy particles (i.e., the CrFeCoNi single-phase FCC structure high entropy alloy prepared above) to the hydroxy silicone oil-modified bisphenol A epoxy resin, wherein the amount of the micron-sized high entropy alloy particles added is 15% of the mass of the hydroxy silicone oil-modified bisphenol A epoxy resin, and stirring at a speed of 1500 r / min for 10 min using a dispersing disk of a vacuum high-speed stirrer, so that the micron-sized high entropy alloy particles and the resin matrix form a uniform mixed slurry;

[0052] The mixed slurry was poured into a three-roll mill for dispersion and grinding with a grinding interval of 50 μm and a rotation speed of 300 r / min.

[0053] (4) The ground mixed slurry was mixed with the PA650 curing agent at a mass ratio of 5:4, and diluted with a n-butanol-xylene mixed solution to a viscosity of about 1000 cps.

[0054] Example 1 Preparation of high entropy alloy / graphite filled hydroxy silicone oil modified bisphenol A type epoxy resin coating

[0055] Here are the steps:

[0056] (1) Preparation of bisphenol A epoxy resin modified with hydroxy silicone oil

[0057] Same as step (1) of Comparative Example 2.

[0058] (2) Preparation of CrFeCoNi single-phase FCC structure high entropy alloy

[0059] Same as step (2) of Comparative Example 3.

[0060] (3) adding graphite with a particle size of 1 μm to the bisphenol A epoxy resin modified with hydroxy silicone oil, wherein the amount of graphite added is 5% of the mass of the bisphenol A epoxy resin modified with hydroxy silicone oil, and stirring at a speed of 1500 r / min for 10 min using a dispersing disk of a vacuum high-speed stirrer, so that the graphite and the resin matrix form a uniform mixed slurry;

[0061] The mixed slurry was poured into a three-roll mill for dispersion and grinding with a grinding interval of 10 μm and a rotation speed of 300 r / min.

[0062] (4) adding micron-sized high entropy alloy particles to the mixed slurry after grinding in the above (3), wherein the addition amount of the micron-sized high entropy alloy particles is 15%, and stirring is performed at a speed of 1500 r / min for 10 min using a dispersion disk of a vacuum high-speed stirrer, so that the micron-sized high entropy alloy particles and the resin matrix form a uniform mixed slurry;

[0063] The mixed slurry was poured into a three-roll mill for dispersion and grinding with a grinding interval of 50 μm and a rotation speed of 300 r / min.

[0064] (5) The mixed slurry after grinding in the above (4) was mixed with the PA650 curing agent at a mass ratio of 5:4, and diluted with a n-butanol-xylene mixed solution to a viscosity of 1000 cps.

[0065] Example 2 Preparation of high entropy alloy / titanium dioxide filled hydroxy silicone oil modified bisphenol A type epoxy resin coating

[0066] Here are the steps:

[0067] (1) Preparation of bisphenol A epoxy resin modified with hydroxy silicone oil

[0068] Same as step (1) of Comparative Example 2.

[0069] (2) Preparation of CrFeCoNi single-phase FCC structure high entropy alloy

[0070] Same as step (2) of Comparative Example 3.

[0071] (3) adding titanium dioxide with a particle size of 50 nm to the bisphenol A epoxy resin modified with hydroxy silicone oil, wherein the amount of titanium dioxide added is 5% of the mass of the bisphenol A epoxy resin modified with hydroxy silicone oil, and stirring at a speed of 1500 r / min for 10 min using a dispersing disk of a vacuum high-speed stirrer, so that the titanium dioxide and the resin matrix form a uniform mixed slurry;

[0072] The mixed slurry was poured into a three-roll mill for dispersion and grinding with a grinding interval of 10 μm and a rotation speed of 300 r / min.

[0073] (4) adding micron-sized high entropy alloy particles to the mixed slurry after grinding in the above (3), wherein the addition amount of the micron-sized high entropy alloy particles is 15%, and stirring is performed at a speed of 1500 r / min for 10 min using a dispersion disk of a vacuum high-speed stirrer, so that the micron-sized high entropy alloy particles and the resin matrix form a uniform mixed slurry;

[0074] The mixed slurry was poured into a three-roll mill for dispersion and grinding with a grinding interval of 50 μm and a rotation speed of 300 r / min.

[0075] (5) The mixed slurry after grinding in the above (4) was mixed with the PA650 curing agent at a mass ratio of 5:4, and diluted with a n-butanol-xylene mixed solution to a viscosity of 1000 cps.

[0076] Example 3 Preparation of high entropy alloy / graphite / titanium dioxide filled hydroxy silicone oil modified bisphenol A type epoxy resin coating

[0077] Here are the steps:

[0078] (1) Preparation of bisphenol A epoxy resin modified with hydroxy silicone oil

[0079] Same as step (1) of Comparative Example 2.

[0080] (2) Preparation of CrFeCoNi single-phase FCC structure high entropy alloy

[0081] Same as step (2) of Comparative Example 3.

[0082] (3) adding titanium dioxide with a particle size of 50 nm to the bisphenol A epoxy resin modified with hydroxy silicone oil, wherein the amount of titanium dioxide added is 2.5% by weight of the bisphenol A epoxy resin modified with hydroxy silicone oil, and stirring the mixture at a speed of 1500 r / min for 10 min using a dispersing disk of a vacuum high-speed stirrer, so that the titanium dioxide and the resin matrix form a uniform mixed slurry A;

[0083] The mixed slurry A was poured into a three-roll mill for dispersion and grinding, with a grinding interval of 10 μm and a rotation speed of 300 r / min.

[0084] (4) adding graphite with a particle size of 1 μm to the mixed slurry A ground in the above (3), wherein the amount of graphite added is 2.5% of the mass of the bisphenol A epoxy resin modified with hydroxy silicone oil, and stirring at a speed of 1500 r / min for 10 min using a dispersing disk of a vacuum high-speed stirrer, until the graphite and the resin matrix form a uniform mixed slurry B;

[0085] The mixed slurry B was poured into a three-roll mill for dispersion and grinding at a grinding interval of 10 μm and a rotation speed of 300 r / min.

[0086] (5) adding micron-sized high entropy alloy particles to the mixed slurry B after grinding in the above (4), wherein the addition amount of the micron-sized high entropy alloy particles is 15%, and stirring is performed at a speed of 1500 r / min for 10 min using a dispersion disk of a vacuum high-speed stirrer, so that the micron-sized high entropy alloy particles and the resin matrix form a uniform mixed slurry C;

[0087] The mixed slurry C was poured into a three-roll mill for dispersion and grinding, with a grinding interval of 50 μm and a rotation speed of 300 r / min.

[0088] (6) The mixed slurry C ground in the above (5) was mixed with the PA650 curing agent at a mass ratio of 5:4, and diluted with a n-butanol-xylene mixed solution to a viscosity of 1000 cps.

[0089] Experiment 1 Performance Test

[0090] The epoxy resin coating slurry obtained by Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 1, Example 2 and Example 3 was diluted to a viscosity of 1000cps after adding PA650 curing agent, and the diluted coating was sprayed on the surface of the aluminum alloy (GB5052) plate using a spray gun. The compressed air pressure of the spray gun was 0.3MPa, the thickness of the cured coating was 80μm, the curing temperature was 65°C, and the curing time was 4h.

[0091] The friction and wear performance was verified using a ring-block friction and wear tester, and the test equipment was a high-speed ring-block tester. The dual part was a GCr15 steel ring (the surface of the GCr15 steel ring was previously polished with 1000-grit water sandpaper to remove the surface oxide layer), with a radius of 30mm and a height of 25mm. The size of the coated aluminum block was 50mm×10mm×4mm. The test conditions were: load 300N, speed 1m / s, experimental duration 120min, and the lubricating medium was 1mL PAO4 base lubricating oil.

[0092] After the friction and wear experiment, the wear scar width was measured using an optical microscope, and the wear rate was calculated using the formula.

[0093] The calculation formula of wear rate is:

[0094]

[0095] Wherein, L′ is the width of the specimen (mm), R is the diameter of the dual steel ring (mm), W is the width of the wear scar (mm), F is the normal force (N), and L is the sliding distance (m).

[0096] Three parallel experiments were conducted and the average value of the calculated results was taken. The friction coefficient bar graph under lean oil condition at high speed and high load is shown in Figure 1 As shown, the wear rate bar graph under lean oil condition, high speed and high load is as follows Figure 2 The data are shown in Table 1.

[0097] Table 1 Dynamic friction coefficient and wear rate

[0098]

[0099]

[0100] Referring to Table 1, it can be seen from Comparative Examples 1, 2 and 3 that the modification of hydroxy silicone oil and the addition of high entropy alloy powder can effectively reduce the friction coefficient and wear rate of epoxy resin. The reason for the analysis may be that the bisphenol A epoxy resin modified with silicone oil can provide friction reduction and wear resistance under oil-poor or even dry friction conditions by relying on the self-lubricating properties of the epoxy resin itself and the dual lubrication mode of releasing silicone oil. Furthermore, the addition of micron-sized high entropy alloy can significantly improve the reinforcing effect of bisphenol A epoxy resin.

[0101] Examples 1, 2, and 3 are based on Comparative Example 3, and the friction and wear properties of the coatings are investigated when graphite, titanium dioxide, and graphite / titanium dioxide are added separately to the high entropy alloy-filled hydroxy silicone oil-modified bisphenol A epoxy resin coating. It can be seen that the addition of graphite alone can only slightly reduce the friction coefficient and wear rate of the coating; after the addition of titanium dioxide alone, the wear rate of the coating does not change much, while the friction coefficient increases to a certain extent; and after the addition of graphite / titanium dioxide at the same time, the friction coefficient and wear rate of the coating are further reduced. This shows that the addition of submicron solid lubricants and nano-scale metal oxide particles can synergistically improve the wear resistance and lubrication properties of the composite material, and solve the friction and wear problems of oil-poor and dry friction conditions before the transfer film is formed.

[0102] In summary, the "large micron-submicron-nano" three-scale epoxy resin coating of the present invention has excellent performance. Coupling high entropy alloy particles, solid lubricants and metal compound particles in the modified matrix can greatly improve the friction and wear performance of the coating product.

[0103] The above examples are provided to those skilled in the art to fully disclose and describe how to make and use the claimed embodiments, rather than to limit the scope of the disclosure herein. Modifications that are obvious to those skilled in the art will fall within the scope of the appended claims.

Claims

1. A method for preparing an epoxy resin coating material suitable for lean lubrication, high load and high speed conditions, characterized in that: The following steps are involved: (1) adding a metal oxide having a particle size of 50 to 100 nm to a hydroxy silicone oil-modified bisphenol A epoxy resin in an amount of 1 to 10% of the hydroxy silicone oil-modified bisphenol A epoxy resin, stirring and grinding to obtain a mixed slurry A; The metal oxide is selected from any one or more of titanium dioxide, aluminum nitride, and aluminum oxide; (2) adding a solid lubricant with a particle size of 0.2 to 2 μm to the mixed slurry A in an amount of 1 to 10% of the hydroxy silicone oil-modified bisphenol A epoxy resin, stirring and grinding to obtain a mixed slurry B; The solid lubricant is selected from any one or a combination of two or more of MoS2, BN, WS2, talc, and graphite; (3) Adding a high entropy alloy to the mixed slurry B in an amount of 5% to 50% of the bisphenol A epoxy resin modified by hydroxy silicone oil, stirring evenly, and grinding to obtain an epoxy resin coating material; the high entropy alloy is a CrFeCoNi single-phase FCC structure high entropy alloy.

2. The method for preparing the epoxy resin coating material suitable for lean oil lubrication, high load and high speed working conditions according to claim 1, characterized in that: In the step (1), the metal oxide is titanium dioxide, the particle size is 50 nm, and the addition amount is 2.5%; And / or: In the step (2), the solid lubricant is graphite, the particle size is 1 μm, and the addition amount is 2.5%; And / or: In the step (3), the addition amount of CrFeCoNi single-phase FCC structure high entropy alloy is 15%.

3. The method for preparing the epoxy resin coating material suitable for lean oil lubrication, high load and high speed working conditions according to claim 1, characterized in that: The CrFeCoNi single-phase FCC structure high entropy alloy is prepared by the following method: taking four metal powders of Cr, Fe, Co and Ni, wherein the molar ratio of the four metal powders is 1:1:1:1; using an electric arc furnace to melt the metal powders; evacuating the furnace; and when the vacuum degree reaches 1×10 -2 After Pa, the metal powder began to melt at a temperature of 1900-2000°C for 30 minutes; then, the CrFeCoNi single-phase FCC structure high entropy alloy powder was prepared by metal atomization technology.

4. The method for preparing the epoxy resin coating material suitable for lean oil lubrication, high load and high speed working conditions according to claim 1, characterized in that: The purity of the metal powder is ≥99.5%; And / or: The specific method of preparing the CrFeCoNi single-phase FCC structure high entropy alloy powder using metal atomization technology is: using a nitrogen-argon mixed gas flow to impact the metal liquid, the superheat of the alloy is controlled at 100-250°C, and the atomization nozzle pressure is 3-6MPa, thereby obtaining the CrFeCoNi single-phase FCC structure high entropy alloy powder.

5. The method for preparing the epoxy resin coating material suitable for lean oil lubrication, high load and high speed working conditions according to claim 1, characterized in that: In the step (1), the bisphenol A epoxy resin modified with hydroxy silicone oil is prepared by the following method: in a nitrogen atmosphere, heating the bisphenol A epoxy resin to 100-180° C., stirring and adding hydroxy silicone oil during the stirring process, wherein the mass ratio of the bisphenol A epoxy resin to the hydroxy silicone oil is 4:1; then adding 0.1%-2.0% of a reaction catalyst, stirring and reacting for 0.5-12 hours, to obtain the bisphenol A epoxy resin modified with hydroxy silicone oil; the reaction catalyst is selected from dibutyltin dilaurate or stannous isooctanoate.

6. The method for preparing the epoxy resin coating material suitable for lean oil lubrication, high load and high speed working conditions according to claim 1, characterized in that: In the steps (1), (2) and (3), the stirring speed is 1500 r / min and the stirring time is 10 min; And / or: In the steps (1), (2) and (3), grinding is performed using a three-roll grinder, wherein in step (1), the grinding spacing is 5 to 10 μm and the rotation speed is 300 r / min; in step (2), the grinding spacing is 5 to 10 μm and the rotation speed is 300 r / min; in step (3), the grinding spacing is 40 to 60 μm and the rotation speed is 300 r / min.

7. The epoxy resin coating material prepared by the method for preparing an epoxy resin coating material suitable for lean lubrication, high load and high speed conditions according to any one of claims 1 to 6.

8. Use of the epoxy resin coating material according to claim 7 in preparing a wear-resistant coating.

9. The use according to claim 8, characterized in that: In specific applications, epoxy resin low-temperature curing agent is added to the epoxy resin coating material, and then a diluent is added to dilute it, and then it is coated on the surface of the workpiece.

10. The use according to claim 9, characterized in that: The epoxy resin low temperature curing agent is selected from any one of an amine curing agent, an anhydride curing agent or an amide curing agent; And / or: the diluent is selected from any one or more of acetone, ethanol, n-butanol and xylene.

Citation Information

Patent Citations

  • High-temperature ceramic organosilicon-phenolic epoxy anticorrosive paint and preparation method thereof

    CN106893448A

  • Anticorrosion weather-proof coating used above ship and warship waterline, and preparation method thereof

    CN109054592A

  • High-stability corrosion-resistant self-lubricating paint, coating and preparation method

    CN109666378A

  • Preparation method of CoCrFeNi high-entropy alloy coating

    CN111945099A

  • Preparation method of high-wear-resistance self-lubricating nano composite material coating

    CN112724788A